Shedding Light on Dark Satellites - Nickerson, Louise Sarah (My University, 2010)
We present a study of satellites in orbit around high-resolution, smoothed particle hydrodynamics (SPH) galaxies simulated in cosmological contexts. For t he galaxies of similar mass to the Milky Way, the luminosity function at redshift zero of the satellites is similar to the observed luminosity function of the system of satellites orbiting the Milky Way. Analysis of the satellites' mass functions reveals an order of magnit ude more dark sat ellites than luminous for each galaxy. There are even dark subhalos more massive than some of the luminous subhalos. What separates luminous and dark subhalos is not their mass at z = 0, but t he maximum mass a subhalo attained over t heir life. We study the effect of four mass-loss mechanisms on the subhalos: ultraviolet (UV) ionising radiation, tidal stripping, ram pressure stripping, and stellar feeclback, and compare the impact each have on the satellites. In the lowest mass subhalos, UV is responsible for most of the gas loss and ram pressure stripping removes the rest. More massive subhalos have deeper potential wells and retain more mass during reionisation. However , as satellites pass near the centre of their main halo , tidal forces cause mass loss from satellites of all masses. It is difficult to discriminate mass loss due to this stellar feedback from other mechanisms using our analysis. During the course of this analysis, we noticed that massive and highly luminous subhalos accrete gas in a region that extends beyond their origins and traces their orbit around the host halo. We also ran a second series of t ests by varying the baryonic physics for a smaller galaxy and found that stellar feedback and UV ionisation do have a profound effect of the subhalos.
Keywords: Astrophysics and Astronomy; Astrophysics and Astronomy